Catalytic Activity of Ni, Co, Mo Supported Anodic Aluminum Oxide Nanocomposites - Anvar Xamidov; Farhodjon Hoshimov; Shavkat Mamatkulov; Khakimjan Butanov; Mirakhmat Yunusov; Olim Ruzimuradov (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
Nanostructured catalysts based on porous aluminum oxide (PAO) and some 3d metals, such as: nickel, cobalt, and molybdenum, have been obtained by anodic oxidation and impregnation. The synthesis of porous aluminum oxide with a highly ordered pore structure with pore sizes of 50 nm and a thickness of 50 µm is carried out by the method of two-stage anodic oxidation. The catalysts are obtained by impregnation of 3d metals into nanosized pores of aluminum oxide. The obtained catalysts based on nickel and porous Al2O3 are studied by scanning electron microscopy (SEM-EDX). The results of SEM-EDX analysis shows that a spongy structure with filament sizes of 100 nanometers containing particles of 3d metals formed on the surface of the aluminum oxide matrix. The results are presented on the activity of nickel and heterogenic cobalt and molybdenum nanoparticles in the reaction of hydrogenation of hexene to hexane. The results show that the yield temperature of the hexane is decreased and the yield of hexane is observed at 200 °C with Ni/Al2O3 catalysts, and a similar yield of hexane mass is achieved at temperatures higher than 250 °C with Co-Mo/Al2O3 and traditional nickel catalysts on kieselguhr. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).